2001
DOI: 10.1029/2000gc000112
|View full text |Cite
|
Sign up to set email alerts
|

Algal and archaeal polyisoprenoids in a recent marine sediment: Molecular isotopic evidence for anaerobic oxidation of methane

Abstract: Analyses of 13C contents of individual organic molecules in a marine sediment show that crocetane, 2,6,11,15‐tetramethylhexadecane, an isomer of phytane, is produced by microorganisms that use methane as their main source of carbon. The sediments lie at a water depth of 68 m in the Kattegat, the strait between Denmark and Sweden. Crocetane appears first 185 cm below the sediment‐water interface, in the zone marking the transition from sulfate reduction to methanogenesis. Its δ13C value is −90 ± 10‰ versus Vien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 77 publications
2
44
0
Order By: Relevance
“…In total, the data presented here provides further support that MOA flourishing near one atmosphere may be adapted to maintain high methane oxidation rates per cell to attain the energy necessary for growth and reproduction. Empirical data of microbial populations and isotopic distributions, as well as theoretical models are also consistent with the growth of MOA near one atmosphere (1,7,31,35).…”
Section: Vol 69 2003 Anaerobic Methanotrophic Archaeal Enrichments mentioning
confidence: 49%
“…In total, the data presented here provides further support that MOA flourishing near one atmosphere may be adapted to maintain high methane oxidation rates per cell to attain the energy necessary for growth and reproduction. Empirical data of microbial populations and isotopic distributions, as well as theoretical models are also consistent with the growth of MOA near one atmosphere (1,7,31,35).…”
Section: Vol 69 2003 Anaerobic Methanotrophic Archaeal Enrichments mentioning
confidence: 49%
“…Both ANME-1 and ANME-2 occur in consortia with relatives of a SRB cluster (Seep-SRB1) within the Desulfosarcina/Desulfococcus branch . Although the geology and biology of a variety of shallow water cold seeps have been well investigated, there is still very little known on the biogeochemistry and relevance of microbial methane consumption (Barry et al, 1996(Barry et al, , 1997Bian et al, 2001;Bussmann et al, 1999;Dando and Hovland, 1992;Garcia-Garcia et al, 2003;Thomsen et al, 2001). The aim of this investigation was to study microbial processes related to methane seepage in shelf sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Many members of the kingdom Archaea also have distinctive lipid signatures because of the unique sn-2, 3 rather than sn-1, 2 stereochemistry of the glycerol moiety and the presence of ether-bound membrane lipids with isoprenoidal carbon skeletons rather than ester-linked alkyl lipids (Koga et al 1998). The lipid signatures of Archaea have even been used to follow the distribution of groups which have not yet been successfully cultured (Bian et al 2001, Sturt et al 2004. Although it has long been suggested that bacterial community structure can be examined through fatty acid profiling (Guckert et al 1985), these acids vary greatly among culturable bacteria and others such as the branched acids do not appear to be universal (Kaneda 1991).…”
Section: Introductionmentioning
confidence: 99%